Opinions of Elite Female Athletes Regarding the Inclusion on Trans Women in the Female Category of Elite Sport - ALEXANDRA SHAW (2023)
Trans women are currently at the forefront of sport due to National Governing Bodies regularly updating their trans inclusion policies, a large online presence from sport stakeholders, and debates in the literature evaluating categorisation methods. However, there is no peer-reviewed literature that has obtained the voices of a large number of elite athletes on trans athlete inclusion in elite sport. The purpose of this study was to provide elite athletes this opportunity to openly voice their opinions, given that they are those directly affected by policy decisions. To achieve this, an anonymous survey was distributed to elite athletes, and they were also given the opportunity to partake in an interview. A total of 123 world class/elite athletes that were eligible for the female category of sport, completed the online survey. Out of this total, 5 athletes were further interviewed. The study compared Current Olympic Sport (COS) versus Olympic Recognised Sport athletes (OR), Tier 4 (elite) and Tier 5 (world class) athletes, as well as COS versus Retired Olympic Sport (ROS) athletes. The survey data established that as a group, current Olympic athletes are against the inclusion of trans women in the female category for contact sports (60.4%) and sports heavily reliant on physical capacity (64.6%). Retired Olympic sport athletes are more supportive of categorisation by biological sex (85%), compared to current Olympic sport athletes (60%) (p=0.050). Elite athletes compared to world class athletes consider that the regulations are more unfair for trans athletes (p=0.022), and world class athletes favour a separate transgender category (p=0.039) more than elite athletes. Further, the themes identified in the interviews included that different benefits are associated with different sports; the different interpretations of fairness; the complex nature of sport; and the importance of representation and how voices are represented. The themes emphasised the importance of representation on athletes’ wellbeing as well as the complexity of sport and athletes’ outlooks. The current thesis highlights how there are differences in attitudes towards fairness, as well as the values and the benefits of sport depending on the group of athletes, the competitive level and the sporting context. Therefore, with the complex nature of sport a blanket approach is no longer the answer.